2016
DOI: 10.1080/09720073.2016.11891924
|View full text |Cite
|
Sign up to set email alerts
|

Facebook and Academic Performance: A Positive Outcome

Abstract: The objective sought with the present paper consists in analyzing the literature about Facebook in order to know the conclusions of the different works with regard to its influence on those results. The examination of 37 papers devoted to this thematic area allows us to know which journals publish more about the impacts that Facebook has on academic performance, which data collection methods are more often used, which topics emerge in parallel to the use of Facebook in the academic context, and which countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Previous researchers had assessed hours of social media use as a dependent variable to assess academic performance (González et al, 2016;Yoo and Kim, 2013). This study examined the factors to categorise the academic usage of social media which explains that, when the students use social media as an online sharing platform and for comprehending any academic topic, accounting undergraduate students can have positive academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers had assessed hours of social media use as a dependent variable to assess academic performance (González et al, 2016;Yoo and Kim, 2013). This study examined the factors to categorise the academic usage of social media which explains that, when the students use social media as an online sharing platform and for comprehending any academic topic, accounting undergraduate students can have positive academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The social media use and the academic outcome was assessed through a frequency table where percentage results were prevalent. Most of the studies focused on the relationship of social media use and educational outcome in general and did not concentrate on a particular subject (Piotrowski, 2015;González, Gasco, & Llopis, 2016;Yu, Shi, & Cao, 2019;Mingle & Adams, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The students who show a more negative attitude toward Facebook are the ones who have never used this social network. Gonzalez, Gasco & Llopis (2016) Analyzing the literature on Facebook and its impact on academic performance leads to conclude that Facebook's positive influence on academic results overshadows its negative influence. Goodband et al (2012) Facebook helps students not only to communicate with one another but also to reinforce their pre-existing friendship ties.…”
Section: Referencesmentioning
confidence: 99%
“…Students who use OSN much are likely to engage in multitasking (doing several academic or other activities concurrently) which diminishes focus and often leads to poor academic performance [48]Moreover, social networking can become addictive, distractive and have negative impact on social interactions, emotional health or cause burnout [2]It has also been noted that OSN leads to reduction in face-to-face interaction among people, sleep problems, anxiety, depression, lack of privacy, fake identity, time consumption and, not infrequently, addiction to social media usage that interferes with performing daily tasks [49,50]Indeed, on an OSN site, there may be so much information overload that it becomes difficult to distinguish the useful from the useless [31]. Students who spend much time on OSN tend to procrastinate and postpone academic work more often [51][52][53] It has been shown that students who use OSN sites everyday have significantly lower grades than those who do not [54].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding academics, students use OSNS to access and share learning resources [3,6,18,28], collaborate and post content online [29], manage and coordinate schedules [5,8,30,31], gain motivation towards serious academic studies [5,32]; participate in peer education through interaction with each other [1, 2, 33]; socialize and enjoy a sense of community belonging [34][35][36], communicate with their instructors [37,38], gratify themselves [39]and get entertainment [7].…”
Section: Literature Reviewmentioning
confidence: 99%